Pengaruh Metode Pembelajaran Team Teaching Terhadap Motivasi Belajar Dan Hasil Belajar Siswa - Tato Octavianto; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of team teaching learning methods on learning motivation, to determine the influence of team teaching learning methods on learning outcomes, and to determine the influence of team teaching learning methods on learning motivation and learning outcomes together. This study uses a causal experimental design method, to determine the effect of the team teaching learning method on learning motivation and learning outcomes of class VII D Even Semester 2022-2023 Academic Year. The population of this study were students of class VII D, totaling 28 students. Samples were taken using the research population because the population was less than 100. Data were collected using interviews, questionnaires and documentation. The data obtained is then tabulated and the percentage calculated. Then testing the hypothesis was processed with SPSS 25. The results of the first T test showed that it was known that the value of the tcount of the learning motivation variable was 0.120. Because the value of tcount < ttable 2.05954. then it can be concluded that H0 or the first hypothesis is accepted. This means that there is no effect of the team teaching learning method on student motivation. The second T test shows that the significance value (Sig.) of the learning outcomes variable is 0.004. Because the value of Sig. 0.004 < probability 0.05, it can be concluded that H0 or the second hypothesis is rejected. This means that there is an influence of the team teaching learning method on student learning outcomes.